Root morphology and phosphorus uptake by potato cultivars grown under deficient and sufficient phosphorus supply - Fernandes, Adalton M. [UNESP]; Soratto, Rogerio P. [UNESP]; Gonsales, Jaqueline R. [UNESP] (Elsevier B.V., 2014)
Information regarding the characteristics that affect P-uptake capacity may assist in the selection of more adapted potato (Solanum tuberosum L.) cultivars and more adequate fertilization management for each cultivar. This study evaluated the P-uptake capacity of potato cultivars (Agata, Asterix, Atlantic, Markies, and Mondial) grown under P-deficient (2 mg L-1) or P-sufficient (31 mg L-1) conditions in nutrient solution and related it to physiological parameters of uptake and morphological root characteristics. When the plants were 24 days old, they were subjected to a P-uptake kinetics study. The length and surface area of roots and the uptake kinetic parameters (I-max, K-m, and C-min) varied among potato cultivars. Phosphorus-deficient potato plants had an approximately 60% smaller root surface area and an increase of 86% in the I-max and net P influx compared with the plants in P-sufficient conditions. However, these modifications in P uptake kinetics can do not influence P acquisition in the soil environment due to very limited P diffusion. The amount of P accumulated by plants grown under P-deficient conditions was directly related to the root length and surface area; a greater root surface, as demonstrated by the Asterix cultivar, is the most important factor for achieving a greater P-uptake capacity. Under P-sufficient conditions, potato cultivars such as Markies and Mondial showed a balance between morphological root characteristics (medium/large length and surface area) and physiological parameters (medium/high I-max values and net P influx) and had a greater P-uptake capacity. However, under field conditions, the responses to P deficiency may be different due to the very limited diffusion of P in the soil and because plants can use additional mechanisms to improve their P uptake from the soil. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Solanum tuberosum; Uptake kinetics; Mineral nutrition; Root length; Root surface area; Phosphorus uptake efficiency